On the application of physical and geological modeling for the interpretation of geophysical data; KazGeo 2010 - Orekhov A. N. Aleksandr Nikolaevich (2010, 2010)
An approach of the authors and justified the creation of physical-geological models of ore objects. The example of adapting an existing model to the conditions of a particular object. The estimation of Setting up physical-geological models in the study of geophysical methods of ore deposits of different genesis.